Contribuições da monitoria para o desenvolvimento de competências socioemocionais em uma universidade particular no Distrito Federal - Coimbras, Elisa Rosa (2023)
This investigation falls within the research area of "Education, Technology, and Communication," within the Graduate Program in Education at the Catholic University of Brasília (UCB). The main objective of this study is to analyze the contributions of academic tutoring in higher education to the development of socioemotional skills. To address the main objective, the study has the following specific objectives: to comprehend the concept of socioemotional skills and the importance of cultivating these competences in higher education; to identify the perception of student tutors regarding their experiences with tutoring; to identify the perception of supervising professors concerning the development of socioemotional skills in academic tutoring; and to identify the perceptions of student tutors about the importance of socioemotional skills promoted through academic tutoring for their professional success. This study is justified by attempting to answer the question: how can the practice of tutoring in higher education contribute to the development of socioemotional skills in student tutors, and how can these enhanced abilities influence their trajectories in the labour market? A mixed-methods descriptive research approach encompassing both quantitative and qualitative components was employed. The data collection procedure involved a questionnaire with both closed and open ended questions, and the data analysis was carried out in alignment with the research objectives. The study was conducted at a private university in the Federal District, involving student tutors and supervising professors from undergraduate courses participating in the institution's tutoring program. The research results demonstrate that tutoring is an effective active methodology for the development of socioemotional skills in higher education, yielding significant benefits for students' success in the labour market.